Estudo de caso: dimensionamento e comparação de vigas de concreto armado utilizando classes de resistência dos grupos I e II segundo a NBR 6118:2014 - Fonseca, Luana Abramoski (2015)
The study of reinforced concrete beams using the Group II resistance classes is still new in the market for Brazilian buildings. An incentive about this was the new revision of the Brazilian standard concrete, which introduced the calculation procedure to carry out the design of structural elements in reinforced concrete with strength classes up to 90MPa. In search of that, a case study of a residential building was done in order to compare the sizing of two beams in reinforced concrete, one of a floor-type building and the other for a transition beam, using the strength classes C30, C50, C60 and C80 to analyze the potential benefits among conventional concrete Group I and the high strength of the group II. Finally, it was concluded that beams with large measurements, as the transition beam, the use of reinforced concrete with large resistance is viable in relation to labor and input costs, besides a possible reduction of measurements. Differently on the floor-type beams, the use of more resistant concrete is not advantageous, since there can be no significant reduction of steel and the cross section.